The Influence of Facilities and Service Quality on Participant Satisfaction BPJS Employment Mojokerto Branch Office - Khoirun Nisak Shabira; Sumainah Fauziah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to investigate the effects of amenities and service quality on participant satisfaction at the BPJS Ketenagakerjaan Mojokerto Branch Office. The process used by applying quantitative descriptive research methodologies is known as quantitative research. This study's goal is to objectively describe the issue using figures. The study's population consists of the 196,378 current workers of the BPJS Ketenagakerjaan Mojokerto Branch Office in 2024. Additionally, the study's sample consisted of 100 responders. The results of the study indicate that participant satisfaction is highly impacted by both the quality of the facilities and the services provided, and that this impact is partially.